A comparison of activity demands between trial matches and in-season matches across multiple teams and seasons in semi-professional, male rugby league players - Doering, Thomas; Elsworthy, Nathan; Callaghan, Dean; Jones, Ben; Teramoto, Masaru; Scanlan, Aaron (Biology of Sport, 2023)
Trial matches are frequently used for team preparation in rugby league competitions, making it essential to understand the demands experienced to assess their specificity to actual competition. Consequently, this study aimed to compare the activity demands between pre-season trial matches and early in-season rugby league matches. Following a repeated-measures observational design, 39 semi-professional, male rugby league players from two clubs were monitored using microsensors during two trial matches and the first two in-season matches across two consecutive seasons. Total distance, average speed, peak speed, absolute and relative highspeed running (HSR; > 18 km·h -1 ) and low-speed running (LSR; < 18 km·h -1 ) distance, as well as absolute and relative impacts, accelerations (total and high-intensity > 3 m·s -2 ), and decelerations (total and highintensity < -3 m·s -2 ) were measured. Linear mixed models and Cohen’s d effect sizes were used to compare variables between match types. Playing duration was greater for in-season matches (p < 0.001, d = 0.64). Likewise, higher (p < 0.001, d = 0.45–0.70) activity volumes were evident during in-season matches indicated via total distance, HSR distance, LSR distance, total accelerations, high-intensity accelerations, total decelerations, and high-intensity decelerations. Regarding activity intensities, a higher average speed (p = 0.008, d = 0.31) and relative LSR distance (p = 0.005, d = 0.31) only were encountered during in-season matches. Despite players completing less volume, the average activity intensities and impact demands were mostly similar between trial and early in-season matches. These findings indicate trial matches might impose suitable activity stimuli to assist players in preparing for early in-season activity intensities.